Nauka języka czeskiego w Czechach dla uczniów posługujących się innym językiem ojczystym - Eliášková, Klára; Hájková, Eva (Studia Edukacyjne, 2024)
The aim of our study is to examine the instruction of the Czech language for students with a dif-ferent mother tongue (DMT students). We provide a brief overview of how language instruction is implemented in Czechia and, based on a research probe into teaching practices, identify the specific aspects and critical challenges. Through a case study, we focus on illustrating suitable methodological approaches for Czech language classes for DMT students, using practical examples to underscore the critical need for enhanced support within communication-oriented language instruction.